Upaya Organisasi Nirlaba (NGO) Bertahan di Masa Pandemi Covid 19 - Muhammad Nur Abdillah (COMMUNICATION MAJOR, 2021)
Abstract The pandemic has an impact on many sectors, causing changes in the pattern of activities carried out in general. The pandemic has also affected non-profit organizations (NGOs), Dejavato is no exception. More than 15 years of existence, the organization located in Semarang has 59 university partners, 34 SMP / MTs partners, 60 SMA / SMK partners, 13 TK / PAUD partners, 21 SD / MI partners, and 20 other foundation partners spread across almost all of the region in Indonesia. This shows that Dejavato has credibility and a strong influence on the local community. The existence of a pandemic makes the Dejavato Foundation to adapt to use online media to survive, because of the cessation of offline activities that result in the achievement of vision threatened to fail. This article aims is to determine the efforts to utilize digital media during the pandemic by the Dejavato Foundation. This research uses a qualitative method with a case study approach where after the data was collected, pattern matching was carried out to validate the data found. The theory that is used in this research is the theory of e-PR and Stakeholder Theory. The primary data was collected through interviews with the founder and public relations coordinator of the Dejavato Foundation, and observation. Meanwhile, to collect the secondary data, the researcher was using the documentation technique. The result of this study shows that Dejavato, in terms of optimizing digital media is by using several methods; convergence of programs, use of e-PR tools, especially social media, dejavatalk, and help empower people online. That shows how much the negative cause in this pandemic, especially for voluntary world.Keywords: Covid-19; Digital Media; Non-Profit Organization; Pandemic; Stakeholder Theory; Volunteering.Abstrak Pandemi Covid-19 memberi dampak pada berbagai sektor tak terkecuali pada NGO (organisasi nirlaba) Dejavato yang memiliki kegiatan utama pengiriman volunteer di berbagai negara. Dejavato merupakan NGO yang telah berdiri lebih dari 15 tahun di Kota Semarang dengan jumlah mitra hingga 207 yang berasal dari mitra TK, SD, hingga perguruan tinggi di Indonesia. Hal tersebut menunjukkan bahwa Dejavato memiliki kredibilitas serta pengaruh yang kuat bagi masyarakat lokal. Adanya pandemi membuat Dejavato Foundation untuk beradaptasi menggunakan media daring untuk bertahan, sebab terhentinya aktivitas luring yang mengakibatkan pencapaian visi terancam gagal. Artikel ini bertujuan untuk mendeskripsikan inovasi yang dilakukan oleh Dejavato Foundation terkait penggunaan media baru dalam menghadapi masa pandemi. Teori yang digunakan dalam penelitian ini adalah teori e-PR serta Stakeholder Theory. Artikel ini merupakan jenis penelitian kualitatif dengan metode studi kasus. Proses pengolahan data dilakukan dengan pengumpulan data, penjodohan pola dan analisis data sesuai dengan teori. Subjek penelitian ini adalah pendiri dan koordinator humas Dejavato Foundation. Hasil penelitian menunjukan bahwa Dejavato melakukan berbagai upaya dalam menghadapi pandemi, yaitu: konvergensi program, pemanfaatan media sosial, mengadakan event dejavatalk, serta membantu memberdayakan masyarakat secara daring. Hal tersebut berarti bahwa pandemi berdampak luas, dan masif bagi dunia sukarelawan.Kata Kunci: Covid-19; New Media; Organisasi Nirlaba; Pandemi; Stakeholder Theory; Volunteering.